The Economic Impact of Covid-19 Pandemic on Female Workers in Serang City, Banten - Wahyu Kartiko Utami; Nikki Prafitri (Universitas Muhammadiyah Malang, 2021)
This research discusses the Covid-19 pandemic and its impact on the female workers economy in Serang City. The Covid-19 pandemic has affected various areas of people's life, including the economy. On the other hand, female workers are among those affected by Covid-19. The theory used in this study is the Cohen economic impact theory which includes the impact on income, the impact on economic activity, and the impact on expenditure. The research method used is qualitative research with a qualitative descriptive approach. Data collection techniques using observation, in-depth interviews, and documentation. This research's informants are the Labor Office of Serang Banten, the Giant Labor Community, and formal female workers. The results showed that the Covid-19 pandemic in Serang City influenced some female workers' economic aspects, such as income, economic activities, and expenditure. This influence is especially for women workers affected, such as female workers at home, who are laid off until their work contract is terminated.